2016
DOI: 10.1063/1.4959126
|View full text |Cite
|
Sign up to set email alerts
|

Locality of correlation in density functional theory

Abstract: The Hohenberg-Kohn density functional was long ago shown to reduce to the Thomas-Fermi approximation in the non-relativistic semiclassical (or large-Z) limit for all matter, i.e, the kinetic energy becomes local. Exchange also becomes local in this limit. Numerical data on the correlation energy of atoms supports the conjecture that this is also true for correlation, but much less relevant to atoms. We illustrate how expansions around large particle number are equivalent to local density approximations and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 92 publications
3
69
0
Order By: Relevance
“…other properties (e.g, ) of both closed-shell and open-subshell cases. This approach has previously been shown to reproduce well the properties of atoms 14,29 . The code is available on request.…”
Section: Model For the Factor In Eq (6); Ionization Potentials Omentioning
confidence: 83%
See 1 more Smart Citation
“…other properties (e.g, ) of both closed-shell and open-subshell cases. This approach has previously been shown to reproduce well the properties of atoms 14,29 . The code is available on request.…”
Section: Model For the Factor In Eq (6); Ionization Potentials Omentioning
confidence: 83%
“…A simple model that accommodates these various physical conditions is Our calculations are carried out in the atomic code pyAtom, which is a python/scipy/numpy implementation of DFT in spherical geometries. We construct the Kohn-Sham orbitals and energies of the atoms and atomic ions using a spherically-symmetric Kohn-Sham potential produced by ensemble averaging 14,28 , that reproduces by construction correct density variables (e.g., ) and…”
Section: Model For the Factor In Eq (6); Ionization Potentials Omentioning
confidence: 99%
“…The overall trend for the total exchange‐correlation contribution is gathered in Figure , showing that C, O, and S yield minima placed at λx0.60.7, while for Si that minimum is found at λx=1, mostly due to the PT2 correlation contribution being somewhat lower than expected in that case. Actually, if we compare the atomic correlation energies provided by the PBE‐QIDH model, when one feeds the model with the PBE, PBE0, PBEH&H, or HF‐PBE orbitals, with respect to reference values, we found that relative errors are reasonably comprised between 19 and 26 %.…”
Section: Resultsmentioning
confidence: 99%
“…Using the self-consistent density for each functional and nearly-exact correlation energies 17 for the rare-gas atoms Ne, Ar, Kr, and Xe, we have computed the relative errors of the various correlation energy functionals in Fig. 1.…”
Section: Correlation Energy At High Density: Analytic Derivationmentioning
confidence: 99%
“…Correlation energy for neutral rare-gas atoms (Ne, Ar, Kr, Xe) with atomic number Z. The numbers are from reference calculation (taken from Ref 17…”
mentioning
confidence: 99%